Physiological effects of a small green space installed on the side of a clinic for outpatients with depression - Harumi Ikei; Harumi Ikei; Chorong Song; Yasuko Sagasaki; Hideki Nozaki; Yoshifumi Miyazaki (Frontiers in Environmental Health)
Depression rates have been rising globally, making it a significant public health concern. Increasing evidence suggests that exposure to natural environments has positive effects on mental health. However, most studies on the restorative effects of nature have focused on healthy individuals, with limited data available on vulnerable populations, such as patients with depression. This study examined the physiological and psychological relaxation effects of viewing a small urban green space (biotope) on outpatients with depression. Conducted in an urban clinical setting, this crossover study involved 28 adult male outpatients with major depressive disorder. The experimental condition involved viewing a biotope outside the clinic, while the control condition involved viewing a building facade. Heart rate variability was used as a physiological indicator, while subjective evaluations were conducted using the modified semantic differential method and the Profile of Mood States 2nd Edition (POMS 2) short version. Results indicated that biotope viewing significantly increased parasympathetic nervous activity while decreasing sympathetic nervous activity. Subjectively, participants reported increased comfort, relaxation, and naturalness. POMS 2 assessments further revealed a significant reduction in negative affect scores and an increase in positive affect scores. This study provides empirical evidence that integrating small-scale urban greenery into clinical environments can promote relaxation and well-being in individuals with depression. Given the high levels of stress in urban populations, particularly in overcrowded cities like Tokyo, incorporating accessible green spaces in urban planning may serve as a viable intervention to mitigate environmental health disparities and improve mental health outcomes.